Effect of cellobiose supplementation on in vitro fermentation activity and bacterial numbers of porcine inocula. Issue 2 (15th July 2017) - Heinritz, S. N.; Weiss, E.; Seifert, J.; Mosenthin, R.; Kuß, S.; Degenhardt, A. G.; Koch, T. J.
Summary: In this in vitro study, the modified Hohenheim gas test (HGT) was applied to determine fermentation activity and bacterial composition of pig's faecal microbial inoculum using different concentrations of cellobiose. Incubation procedures included normal buffered and osmotic stress conditions (elevated medium salinity). After 24 hr of fermentation, production of gas, ammonia and short‐chain fatty acid (SCFA) was measured, and the gene copy numbers of total bacteria, Lactobacillus spp., Bifidobacterium spp., Roseburia spp., Clostridium Cluster IV spp. and Enterobacteriaceae were analysed using real‐time polymerase chain reaction. There was a significant reduction in gas production after 24 hr when comparing osmotic stress conditions with normal buffered conditions. Under osmotic stress, increasing cellobiose concentrations linearly increased gas production ( p  <   .001), while ammonia, acetic acid and isobutyric acid concentrations decreased ( p  <   .001, p  =   .012, p  =   .035 respectively). Under normal buffered conditions, Roseburia spp. gene copies linearly increased with increasing cellobiose concentrations ( p  =   .048). Lactobacillus spp. and Bifidobacterium spp. numbers were higher under osmotic stress ( p  <   .001) compared to normal conditions. Results might point towards a positive impact of cellobiose supplementation on gut health especially under osmotic stress conditions.